Hot Topics in Echocardiography - Squeri, Angelo (IntechOpen, 2013)
Echocardiography is still the most used imaging technique for the evaluation of cardiac anatomy and function and today it plays an essential role in daily decision making. The echocardiographic technology and its applications have widely developed in the last years leading to a better diagnostic accuracy. On the other hand echocardiography specialists have new clinical questions to answer. Echocardiography meets the growing need for non-invasive imaging in the expanding heart failure population and during structural heart interventions. The new percutaneous therapies need, a precise evaluation of cardiac dimensions and a complete understanding of the spatial relationships between cardiac structures. Echocardiography is of paramount importance both during the patient evaluation and guiding the procedure. This book tries to give an in depth evaluation about the specific issues that a modern cardiovascular imaging specialist is asked to answer nowadays.